Abrupt cooling over the North Atlantic in modern climate models - Giovanni Sgubin (Nature Portfolio, 2017)
Concerns on climate change include the risk of abrupt cooling in the North Atlantic. Here, the authors analyse CMIP5 projections and show that a convection collapse in the subpolar gyre can cool this region by up to 3°C in 10 years, which is as likely to occur by 2100 as a continuous warming.